(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: Analyze critically the “1st Brazilian Recommendation for Biofilm Management in Chronic and Complex Wounds” (from Portuguese, “1a Recomendação Brasileira para o Gerenciamento de Biofilme em Feridas Crônicas e Complexas”). Method: Reviewing information contained in said document according to current literature. Results: The publication was showed to lack methodology compatible with its title; gaps in the recommendations were perceived regarding evidence classification, as well as an absence of grounding from important international consensus, published in the last three years, about treatment of complex wounds with suspected biofilm. Conclusion: The document was concluded to be inadequate for use as a clinical guideline, being considered only a bibliographic review about the theme.